ANALYSIS OF STUDENT’S PROBLEM-SOLVING ABILITIES AS AN EFFORT TO IMPLEMENT THE STEM-BASED MICROLEARNING APPROACH - Ekasari, Aprilita; Yuliatun, Tutik (Universitas Negeri Medan, 2024)
Advancements in science and innovation influence the progress of education in Indonesia. The current situation in Indonesia is characterized by a lack of competent human resources (HR). Quality education helps students develop the values they need for life. The purpose of this research is to describe students' problem-solving abilities so that the implementation of the STEM-based Microlearning approach can yield optimal results. The research will be conducted in the eighth-grade class of Ibn Sina Islamic Middle School. A quantitative descriptive approach is used in this research. A set of 10 problem-solving based descriptive questions is the instrument used in this research. The instrument to be used has been validated. The expert validation results for the questions yielded an average score of 95.33. Data analysis results show that students' problem-solving abilities on the